Her brother's keeper - Kupari, Mike (Baen, 2016)
"It's been years since Catherine Blackwood left the stodgy, repressive colony world of Avalon. Now the captain of the privateer vessel Andromeda, she is a master of her own destiny. But Catherine soon finds herself back on Avalon after receiving a plea from her estranged father, esteemed Avalon Council member Augustus Blackwood. It seems Catherine's brother Cecil, heir to the Blackwood aristocracy, has been taken hostage on the failed world of Zanzibar. Augustus, knowing Catherine is the only one who can be trusted to return Cecil safely, hires her to bring her brother home. To save her brother, Catherine must face down danger at every turn and uncover a mystery four million years in the making"--